2015
DOI: 10.1165/rcmb.2014-0118oc
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Specific Fos-Related Antigen-1 Regulates Cigarette Smoke–Induced Lung Inflammation, Not Emphysema, in Mice

Abstract: Heightened lung inflammation is a cardinal feature of chronic obstructive pulmonary disease (COPD). Cigarette smoke (CS)-induced macrophage recruitment and activation, accompanied by abnormal secretion of a number of inflammatory cytokines and matrix metalloproteinases, play a major role in the pathophysiology of COPD. The Fos-related antigen-1 (Fra-1) transcription factor differentially regulates several cellular processes that are implicated in COPD, such as inflammation and immune responses, cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Fra-1 affects the differentiation and activation of immune cells, especially macrophages, as well as the secretion of many cytokines ( 17 , 121 , 133 , 138 , 142 , 198 , 199 ), but the specific mechanism remains to be further explored. The regulation of the immune response of Fra-1 makes its intracellular expression affect the outcome of many diseases, such as sepsis ( 149 ), atherosclerosis ( 155 ), myocardial infarction ( 101 ), psoriasis ( 134 ), colitis ( 162 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Fra-1 affects the differentiation and activation of immune cells, especially macrophages, as well as the secretion of many cytokines ( 17 , 121 , 133 , 138 , 142 , 198 , 199 ), but the specific mechanism remains to be further explored. The regulation of the immune response of Fra-1 makes its intracellular expression affect the outcome of many diseases, such as sepsis ( 149 ), atherosclerosis ( 155 ), myocardial infarction ( 101 ), psoriasis ( 134 ), colitis ( 162 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, oxidative stress can promote the development of lung inflammation and form a chronic state of mucus secretion. The Fos-related antigen-1 (Fra-1) transcription factor is thought to play a key role in promoting chronic cigarette smoke- (CS-) induced lung macrophagic inflammation in vivo and experiments have shown that the absence of Fra-1 in mice bone marrow can reduce the expression of inflammatory factors and the aggregation of macrophages in the lung [ 34 ]. Additionally, Fos-related antigen-2 (Fra-2) expression has also been described in COPD for the upregulation of monocyte-derived macrophages upon CS stimulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most upregulated mRNAs were Fosl1, Chil3, Lcn2, and Serpina3n (Figure 3A). Fosl1, also known as Fra-1, regulates inflammatory reactions in a cell-dependent manner in mice with cigarette-smoke-induced lung inflammation [40]. Chil3 is also related to the immune response [41,42].…”
Section: Potential Regulation Mechanisms In Cp-aki Micementioning
confidence: 99%